A clinical and demographic analysis of oral pemphigus vulgaris: A retrospective cross‐sectional study from 2001 to 2021 - Muhanad L. Alshami; Fawaz Aswad; Bashar Abdullah (Health Science Reports, 2022)
Abstract Background and Aims Pemphigus vulgaris is an autoimmune vesiculobullous mucocutaneous disorder with life‐threatening consequences. Early detection and adequate care are crucial for a good prognosis. This study aimed to determine the demographic data, clinical features, and the prognosis of patients with oral pemphigus vulgaris. Materials and Methods From 2001 to 2021, all diagnosed oral pemphigus vulgaris cases were extracted. Each patient's demographic and clinical data were gathered. Patients were called via phone to assess the prognosis, treatment type, and specialty of the physician who provided the diagnosis and therapy. Results The majority of the patients had only oral lesions with higher prevalence in female who also expressed severe pain than male. Only 14 of 29 patients responded phone calls. Except for one, all patients were in active disease. More than half of those respondents said pemphigus negatively affects social behavior and food intake. Correct diagnosis and treatment were decided by dermatology, oral medicine, and maxillofacial surgery specialists. Conclusion Oral pemphigus vulgaris was prevalent in females. Severe pain was common in females and older people. Even with effective therapy, the prognosis was poor. Medical and dental professionals had little knowledge of pemphigus vulgaris. Patients frequently report poor quality of life.